BUREAUCRATIC BEHAVIOR MODEL IN POLICY IMPLEMENTATION TO ENHANCE EQUAL AND EXTENSIVE EDUCATION ACCESS (THE DEPARTMENT OF EDUCATION AND CULTURE GORONTALO DISTRICT) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to define a bureaucratic behavior model in the implementation of thepolicies of enhancing equal and extensive education access to deliver educational services.To develop the behavior model, I hinge on the theory of behavior by Draha (1989), whodescribes bureaucratic behaviors as an interplay between individual and bureaucracycharacters. This research brings into focus the development of a behavior model in publicpolicy implementation.This research is carried out in the Department of Education andCulture Gorontalo District Gorontalo Province, one of the provinces in the eastern part ofIndonesia. It is conducted using the qualitative descriptive method, and researchinformants are all employees involved in policy implementation in the research area. Twodata types, i.e., primary (documents, photographs, and picture) and secondary (interviewresults and other research findings, and so forth), are used.Based on the results, there areseveral bureaucratic behavior factors which affect the enhancement of equal and extensiveeducation access. The factors can be categorized into two, i.e., (a) behavior factors whichboost successful policy implementation and (b) behavior factors which inhibit successfulpolicy implementation to enhance equal and extensive education access.Predicated on theresults, I develop a policy behavior model with three cardinal variables of bureaucraticbehaviors. The three factors are (a) individuals’ characters within the organization, (b)bureaucratic characters, and (c) value characters in a bureaucracy culture. The interactionamong the three characters is known as the Value Interaction Behavior (VIB).Using thismodel, it is expected that the mindset of bureaucratic behaviors, which is limited to beperformance achievement-oriented, is changed to be a public-oriented one. Additionally, itis expected that the shift of ethical values can be manifested through turning thebureaucracy-oriented paradigm to be service-oriented by highlighting the values ofopenness, responsibility, and public accountability.